Bankcrupty Analysis of Manufacturing Companies Registered on the Jakarta Islamic Index (JII) Based on the Altman Z-Score Method for the 2019-2021 Period - Sohibi Putri Siregar; Nurlaila Nurlaila (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
When costs exceed income, one of the most frequent issues a firm faces is bankruptcy. Analyzing the index of income and spending is crucial for a business to avoid bankruptcy. The goal of this study is to examine manufacturing businesses that are listed on the Jakarta Islamic Index (JII) that have filed for bankruptcy between 2019 and 2021. Using a population of 30 manufacturing enterprises that are registered on JII, this study employs a quantitative descriptive research design. Next, three sample companies—PT Indofood CBP Sukses Makmur Tbk, PT Unilever Indonesia Tbk, and PT Kalbe Farma Tbk—were collected using the purposive sampling approach utilized in this study. The data analysis approach employs five variables with the Altman Z-score method. The study's findings indicate that PT Indofood CBP Sukses Makmur Tbk has faced significant financial difficulties in the last period (2021). Later, PT Unilever Indonesia Tbk, which was also dealing with severe financial issues, experienced the same scenario. This firm, in contrast to PT Kalbe Farma Tbk, is regarded as safe because it has no issues with its financial situation.